Pengaruh Pupuk Kascing Terhadap Kemampuan Mengikat Air pada Tanah Lempung dan Lempung Berpasir - Monica Rina Tutkey; Fatchan Nurrochmad; Sri Harto Brotowiryatmo (Jurnal Irigasi, 2017)
The water saving irrigation would be better if the soil can hold water maximally. The problem is the soils have different water holding capacity, some of them are less, so there is need to maximize the water holding capacity. Adding  compost with the right composition can improve the soil physical properties, since organic matter in it has the aggregation capability that can bind the small granules to the large granules to improve the water holding capacity. This study aimed to analyze the maximum water holding capacity by adding 0%, 29%, 33%, 40%, 50%, 60%, 67% and 71% of vermicompost on loam and sandy loam soil. Each sample is repeated three times. PF curve was used to determine water holding capacity. The result shows that the maximum water holding capacity of loam soil is 19,14% by adding 40% of vermicompost or increased 13.56% from the original soil. On the other hand, adding vermicompost on sandy loam tends to decrease the water holding capacity. The maximum water holding capacity of sandy loam is 27.87% in 0% (original soil) of vermicompost. Further  research can be continued by paddy plot trial using the best vermicompost composition and the water saving  irrigation method.